Do Website Quality Attributes Influence Customer Satisfaction Towards Online Food Ordering System? - Diviyasheni Kumaran; Nusrah Samat; Lee , Eva Yin Tan (AID Conference, 2020)
Purpose of the study: Online food ordering system is really in trend nowadays due to the increasing use of Internet. One of the key challenges of online food business is how they manage the online food ordering system, which holds a significant importance to customer satisfaction. This study tries to investigate the relationship between online food ordering system’s website quality attributes with customer satisfaction. Methodology: Self-administered questionnaire was developed to collect the data. Online survey was used in getting the feedback from targeted young adults that use online food ordering system. A total of 211 sets of questionnaires were received through the online survey. Data was then analysed using frequencies and descriptive statistics, reliability, correlation, and regression analyses. Main Findings: The Cronbach’s alpha values varied from between 0.90 to 0.92. The variance proposes consistent and reliable scales used in this study. Customer satisfaction has a strong α coefficient of 0.92 based on responses of the data collection. Findings indicated that three out of five website quality attributes have significant influence towards customer satisfaction. They are website design (β= 0.306, p< 0.01), website information quality (β= 0.368, p< 0.01) and website intelligence (β= 0.223, p< 0.05). Website quality attributes like website design, payment system and website intelligence should be updated accordingly to meet customer expectation which leads to customer satisfaction.